Identifikasi Jamur Penyebab Onikomikosis Pada Pedagang Ikan di Pasar Kota Palangka Raya - Fitria Hariati Ramdhani (Jurnal Skala Kesehatan, 2026)
Fish tradings are considered an occupational group at high risk for mycotic infections due to continuous water exposure, which creates a moist environment favorable for fungal growth. This study aimed to identify fungal species causing onychomycosis in fish trading nails using culture on Sabouraud Dextrose Agar (SDA) and confirmation by 10% potassium hydroxide (KOH) microscopic examination. The method used in this study was experimental. Results of microscopic examination revealed positive in 13 samples (87.7%) and negative in 2 samples (13.3%). The findings indicate that the majority of fish traders’ nails at Palangka Raya City Market are infected with non-dermatophyte fungi as the cause of onychomycosis.